A comprehensive study on the performance of alkali activated fly ash/GGBFS geopolymer concrete pavement. Issue 8 (3rd August 2022) - Badkul, Aishwarya; Paswan, Rakesh; Singh, S. K.; Tegar, J. P.
Abstract : Geopolymer concrete is gaining a lot of attention among researchers across the globe due to its potential contribution to sustainability. Several studies have considered the use of geopolymer concrete for structural elements, but limited attempts have been made on its application in rigid pavements. The current paper investigates the mechanical and durability properties of pavement quality geopolymer concrete (PQGC) produced by varying the amount of alkali concentration and GGBFS content. The results obtained were correlated with compressive strength of PQGC and compared to control cement concrete. It was found that upon increasing the activator concentration and amount of GGBFS content significant increase in performance of PQGC can be attained. However, the increase in activator concentration above 12M and inclusion of GGBFS above 28% doesn't show any significant impact. The design thickness calculated as per Indian Road Congress (IRC 58) using the mechanical properties obtained for PQGC was also found less than the control cement concrete.